The Illusion of Well-Being : Economic Policymaking Based on Respect and Responsiveness - White, Mark D.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
This book will argue against the use of well-being to guide policymaking and in favor of a rule-oriented approach to policymaking that respects the choices of individuals.
Keywords: Science; Science; Science, general